2021
DOI: 10.1001/jama.2021.2384
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator Weaning and Discontinuation Practices for Critically Ill Patients

Abstract: for the Canadian Critical Care Trials Group IMPORTANCE Although most critically ill patients receive invasive mechanical ventilation (IMV), few studies have characterized how IMV is discontinued in practice.OBJECTIVE To describe practice variation in IMV discontinuation internationally, associations between initial discontinuation events and outcomes, and factors associated with the use of select discontinuation strategies and failed initial spontaneous breathing trials (SBTs). DESIGN, SETTING, AND PARTICIPANT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 32 publications
3
62
0
9
Order By: Relevance
“…Although many predictive indices and clinical tools are already in use [1,[13][14][15][16][17][18][19][20][21][22], >20% of the patients who have fulfilled the classic weaning criteria require reintubation [14,[23][24][25]. The predictive performance decreases in patients with multi-organ dysfunction, older age, prolonged MV, and severe illness [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Although many predictive indices and clinical tools are already in use [1,[13][14][15][16][17][18][19][20][21][22], >20% of the patients who have fulfilled the classic weaning criteria require reintubation [14,[23][24][25]. The predictive performance decreases in patients with multi-organ dysfunction, older age, prolonged MV, and severe illness [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The exact causes of failed ventilator weaning are still debatable, but recent studies have shown that 60% of such cases could be avoided. [3][4][5][6] This suggests that the current evaluation system needs to be improved by introducing new indicators, especially those that reflect patients' pulmonary ventilation dynamics before and after ventilator weaning.…”
Section: Introductionmentioning
confidence: 99%
“…Bei der NIV wird der Patient entweder über eine Gesichtsmaske oder einen Helm an das Beatmungsgerät angeschlossen. Grieco et al [9] verglichen in einer multizentrischen, randomisierten klinischen Studie die frühe 48 18 Tage [IQR: 0-22] für HFNO, p = 0,26). Einige klinisch wichtige sekundäre Ergebnisse unterschieden sich zwischen den Gruppen: eine signifikant niedrigere Inzidenz von Intubationen in der Helm-NIV-Gruppe (30 vs. 51 % für HFNO, p = 0,03), und die mediane Anzahl der Tage ohne invasive mechanische Beatmung innerhalb von 28 Tagen war in der Helm-NIV-Gruppe signifikant höher als in der HFNO-Gruppe (28 Tage [IQR: [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] vs. 25 Tage [IQR: 4-28], p = 0,04).…”
Section: Originalpublikationunclassified
“…Grieco et al [9] verglichen in einer multizentrischen, randomisierten klinischen Studie die frühe 48 18 Tage [IQR: 0-22] für HFNO, p = 0,26). Einige klinisch wichtige sekundäre Ergebnisse unterschieden sich zwischen den Gruppen: eine signifikant niedrigere Inzidenz von Intubationen in der Helm-NIV-Gruppe (30 vs. 51 % für HFNO, p = 0,03), und die mediane Anzahl der Tage ohne invasive mechanische Beatmung innerhalb von 28 Tagen war in der Helm-NIV-Gruppe signifikant höher als in der HFNO-Gruppe (28 Tage [IQR: [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] vs. 25 Tage [IQR: 4-28], p = 0,04). Diese wichtige Studie ist die erste, die Helm-NIV vs. HFNO bei Patienten mit einer relativ homogenen Ursache für akutes hypoxämisches respiratorisches Versagen ("acute hypoxemic respiratory failure", AHRF) direkt verglichen hat.…”
Section: Originalpublikationunclassified
See 1 more Smart Citation